KUALITAS PELAYANAN TRANSPORTASI PUBLIK WIRA WIRI SUROBOYO - Utami, Fania Khalsa; Maratus, Laili Dwi; Sherlyta, Bella Ayu; Irianti, Rahma Ayu; Wahyudi, Kalvin Edo (PREDIKSI : Jurnal Administrasi dan Kebijakan, 2025)
Surabaya City is one of the most densely populated areas in East Java. High density also results in higher traffic in Surabaya City. So this makes the government try to make a new plan to reduce traffic congestion by making public transportation innovations, namely Wira Wiri Suroboyo. The purpose of this study was to determine the quality of Wira Wiri Suroboyo public transportation services. This research method uses quantitative descriptive analysis with the approach of public service quality theory which includes 5 indicators, namely, tangibles, reliability, empathy, assurance, and responsiveness, and data collection is done by distributing questionnaires distributed to people who have used Wira Wiri Suroboyo services. The results of this study indicate that the recapitulation of Wira Wiri Suroboyo service quality assessment in the good category with a value of 76.1%. In the Tangibles Indicator 67% in the good category, Reliability gets a good score of 72%, Responsiveness gets a good score of 73.2%, Assurance gets a good score of 73.5%, and Empathy gets a good score of 71.5%. However, in tangible indicators which have the lowest percentage, it is necessary to improve facilities and infrastructure such as air conditioning and seating so that passengers are safer and more comfortable.